Successful cochlear implantation in Langerhans cell histiocytosis: A rare case. (4th March 2018) - Gupta, Gaurav; Jain, Avani; Grover, Mohnish
Abstract : An 8-year-old girl presented with a 1-year history of bilateral progressive hearing loss and vertigo for 6 months. High-resolution computed tomography of the temporal bones demonstrated multiple lytic lesions. Histopathology examination confirmed a diagnosis of Langerhans cell histiocytosis (LCH). She underwent chemotherapy for 12 months. Following treatment, she was in remission. However, the bilateral profound sensorineural hearing loss persisted. She underwent right cochlear implantation with very good functional audiological outcomes. This is the first known reported case of successful auditory rehabilitation through cochlear implantation in a patient with bilateral profound hearing loss due to isolated bilateral temporal bone LCH.